Public Policies of Infamy: Four Cases in Health - Mexico - Donovan Casas Patiño; Alejandra Rodríguez Torres; Mario Rodolfo Salazar Morales (Archives of Community Medicine and Public Health - Peertechz Publications, 2017)
This article invites to a transdisciplinary refl ection, in which the policies should be part of the social benefi t in this health case, here are presented four elements of analysis, maternal mortality, homicide, chronic noncommunicable diseases and ecocide. Thus these elements show a state in fl ight that on the one hand, ignores the real social problems in health and on the other, signs perverse pacts and creates public policies out of context dictated by neoliberal interests. In this way a transdisciplinary refl ection on health is presented, where Mexico is present sailing in an infi nite sea of oblivion and political perversion.